Principle of justice adversarial and equal rights in criminal proceedings (Journal of actual problems of jurisprudence, 2019)
In a preliminary investigation and trial of cases to any citizen, brought in as a suspect, accused or defendantConstitution of the Republic of Kazakhstan and the Criminal – Procedural Code of the Republic ofKazakhstan shall have the right to be protected from prosecution.Inalienable, natural right to defend arisesfrom the competitive structure of the process, when a strong charge to resist adequate protection.The highestdegree of protection of the rights and lawful interests of individuals, the more the person involved in theorbit of the criminal justice is the hallmark of a democratic and legal state.Keywords: competitiveness, equality, equal rights,accusation, protection, justice